Adenosine-guided pulmonary vein isolation versus conventional pulmonary vein isolation in patients undergoing atrial fibrillation ablation: An updated meta-analysis. (15th January 2017) - Papageorgiou, Nikolaos; Providência, Rui; Srinivasan, Neil; Bronis, Kostas; Costa, Francisco Moscoso; Cavaco, Diogo; Adragão, Pedro; Tousoulis, Dimitris; Hunter, Ross J.; Schilling, Richard J.; Segal, Oliver R.; Chow, Anthony; et al.
Abstract: Background: Recurrent atrial fibrillation episodes following pulmonary vein isolation (PVI) are frequently due to reconnection of PVs. Adenosine can unmask dormant conduction, leading to additional ablation to improve AF-free survival. We performed a meta-analysis of the literature to assess the role of adenosine testing in patients undergoing atrial fibrillation (AF) ablation. Methods: PubMed, EMBASE, and Cochrane databases were searched through until December 2015 for studies reporting on the role of adenosine guided-PVI versus conventional PVI in AF ablation. Results: Eleven studies including 4099 patients undergoing AF ablation were identified to assess the impact of adenosine testing. Mean age of the population was 61 ± 3 years: 25% female, 70% with paroxysmal AF. Follow up period of 12.5 ± 5.1 months. A significant benefit was observed in the studies published before 2013 (OR = 1.75; 95%CI 1.32–2.33, p  < 0.001, I 2  = 11%), retrospective (OR = 2.05; 95%CI 1.47–2.86, p  < 0.001, I 2  = 0%) and single-centre studies (OR = 1.58; 95%CI 1.19–2.10, p  = 0.002, I 2  = 30%). However, analysis of studies published since 2013 (OR = 1.41; 95% CI 0.87–2.29, p  = 0.17, I 2  = 75%) does not support any benefit from an adenosine-guided strategy. Similar findings were observed by pooling prospective case-control (OR = 1.39; 95%CI 0.93–2.07, p  = 0.11, I 2  = 75%), and prospective randomized controlled studies (OR = 1.62; 95%CI 0.81–3.24, p  = 0.17, I 2  = 86%). Part of the observed high heterogeneity can be explained by parameters such as dormant PVs percentage, use of new technology, improvement of center/operator experience, patients' characteristics including gender, age, and AF type. Conclusions: Pooling of contemporary data from high quality prospective case–control & prospective randomized controlled studies fails to show the benefit of adenosine-guided strategy to improve AF ablation outcomes. Highlights: This updated meta-analysis assesses the role of adenosine testing in patients undergoing atrial fibrillation (AF) ablation. Pooling of contemporary data fails to show the benefit of adenosine-guided strategy to improve AF ablation outcomes. Our meta-analysis questions the role of adenosine testing in AF ablation and highlights the need for high quality data.